Eficacia del control quimico de la nueva plaga de las palmeras Rhynchophorus ferrugineus (Olivier, 1790)(Col.: Curculionidae) - Barranco, P.=700 1 De la Peña, J.; Martin, M.M.; Cabello, T.
(Es, En)
ilus., 9 ref.
Keywords: RHYNCHOPHORUS FERRUGINEUS; PALMAE; CONTROL QUIMICO; PLAGUICIDAS; CONTROL BIOLOGICO; EXTRACTOS VEGETALES; AZADIRACHTA INDICA; ESPAÑA; GORGOJO ROJO DE LAS PALMERAS; PIPRONIL